(untitled) (Research, Society and Development, 2021)
"Cancer" is a generic term for a very large group of diseases that can affect any part of the body. They can occur due to external factors such as the environment, or internal, in which, from the formation of cancer, damage occurs in cellular deoxyribonucleic acid: the terms used to describe these earlier changes until the formation of the disease are oncogenesis or carcinogenesis. The influence of psychological, behavioral and social aspects on the evolution and remission of cancer is perceived. Cognitive-Behavioral Therapy is a therapeutic approach that seeks to study and evidence results from cognitive and/or behavioral interventions; it is a model of structured and short-term therapeutic treatment, which can be applied in relation to cancer and the problems associated with or resulting from it. The objective is to analyze the applicability of CBT in cancer patients. This is an integrative literature review study carried out on the basis of the Virtual Health Library and PubMed between 2010 and 2020. 14 studies were selected, containing randomized clinical trials, interventions that applied psychoeducation, relaxation, problem solving and stress management carried out in group and/or online modalities. In addition, the prevalence of topics such as: quality of life, anxiety, depression, fatigue and body image related to cancer patients was identified. It was found that the application of CBT is an effective approach for the treatment of issues related to illness, whether through groups, individual, online, in person or through electronic applications, which can enable and contribute significantly to the treatment of people with cancer.